TBu3P/ZnR2 (R=Et, I) Frustrated Lewis Pair Catalysts for Functionalization and Reduction of CO2. Issue 2 (6th November 2014) - Dobrovetsky, Roman; Stephan, Douglas W.
Abstract The functionalization and reduction of CO2 are important targets not only because of concerns about its accumulation or the impact of this greenhouse gas on Earth's climate, but also because of its potential as a C‐1 feedstock. In this work, both functionalization and reduction of CO2 were performed using tBu3P/ZnR2 (R=Et, I) "frustrated Lewis pairs" (FLPs). Phosphine‐catalyzed carboxylation of alkyl‐Zn bonds and catalytic reduction of CO2 using silanes as hydride sources and tBu3P/ ZnR2 (R=Et, I) FLPs as catalysts are reported. This is also the first time Zn‐based FLP chemistry in functionalization of CO2 is reported.